Medical confidentiality and legal privilege - McHale, Jean V. (Jean Vanessa), 1965- (Social ethics and policy series., 1993)
McHale asks why a doctor can be forced to disclose a patients' confidences in court when other professional confidences are protected. She goes on to look at whether doctors keep patients' confidences and the need for statutory reform.